Cathedral of St. Paul at 136 Tremont Street, ca. 1870 - Ward, Joseph and Son (Tufts Archival Research Center, 2005)
Street-level view northeast of the Cathedral of St. Paul, located at 136 Tremont Street. The facade of the church faces north-northwest. 133-134 Tremont Street are included along the left side of the carte-de-visite. Street lamps and wrought iron fencing line Tremont Street. 3 x 2 5/16, 3 15/16 x 2 3/8 overall Cartes-de-visite